Sustained Complete Response to Cytotoxic Therapy and the PARP Inhibitor Veliparib in Metastatic Castration-Resistant Prostate Cancer – A Case Report - VanderWeele, David J. (Front Oncol, 2015)
Solid tumors harboring BRCA1 or BRCA2 mutations have been shown to respond to PARP inhibitors. These responses are partial and transient. In this case report, we describe an 82-year-old male with poorly differentiated prostate cancer with metastases to the lung, liver, abdomen, and bowel. Molecular testing demonstrated alterations in BRCA2, ERG, and TP53. Based on this result, he was enrolled in a therapeutic trial and received carboplatin, gemcitabine, and veliparib, to which he had a partial response. He continued to respond while on veliparib maintenance alone, and after 38 cycles he had a sustained complete response. A sustained complete response to PARP inhibitor-based therapy has not previously been described for prostate cancer. This case suggests that cytotoxic therapy in combination with PARP inhibitors may yield exceptional responses, and molecular studies may help guide patient selection for these therapies.